The Influence of Financial Literacy, Lifestyle and Parental Socioeconomic Status on Personal Financial Management - Yuan Yulio Pramudia; Nurhailza (Journal of Management and Digital Business, 2024)
Purpose -  This study aims to analyze the influence of financial literacy, lifestyle and parental socioeconomic status on personal financial management. This study emphasizes the importance of financial literacy education, lifestyle control and parental socioeconomic support in enhancing student’s personal financial management.  Design/methodology/approach – The research employs a quantitative methods with a correlational approach. This study utilized questionnaires distributed to undergraduate students from both public and private universities, specifically those from the 2020 – 2024 academic cohorts. A total of 609 questionnaires were disseminated via social media platforms, each containing 32 statements to be answered by respondents. Out of these, 201 responses were received, originating from 10 regions. To analyze the data and derive the results, the researcher employed PLS – SEM Version 3.0. Findings - The results of this study reveal that financial literacy has a positive and significant effect on personal financial management, lifestyle positively and significantly influences personal financial management and parental socioeconomic status positively and significantly impacts personal financial management. Respondents with good financial literacy are more capable of managing their expenses, whereas a consumptive lifestyle tends to pose challenges in financial management. Research limitations/implications  - The focus is to understand the relationship between these independent variables and financial management behavior, considering the importance of financial management in supporting students financial stability.